Mughal Documents (1526-1627) - Tirmizi, S.A.I., (Brill | Manohar Publishers & Distributors, 2024)
This book seeks to present an integrated study of 350 Mughal documents covering the period from 1526 to 1627 and spanning the reigns of Babur, Humayun, Akbar and Jahangir. It gives a general idea of the nature, contents and territorial range of the documents and assesses their value for reconstructing the history of Mughal India, which has hitherto been largely based on chronicles, travelogues, manual, etc. It shows that the Mughals modelled their documentary practices after those prevalent in their homeland and those followed by their Turko-Afghan predecessors.